Nursing management after interventional therapy in five patients with acute superior mesenteric artery embolism (5例急性肠系膜上动脉栓塞介入治疗的术后护理) - WU Xiaoling (吴晓玲); JING Jing (敬婧); TANG Ni (汤妮) (中西医结合护理)
This paper reviewed the nursing management and complication observation after interventional therapy in five patients with acute superior mesenteric artery embolism. Postoperative complications included bowel necrosis, intra-abdominal hemorrhage and hemorrhage at wound site. A comprehensive nursing management, including illness observation, complication identification and predictive nursing, is required to reduce the risk of death and improve the rehabilitation. (本文回顾性分析了5例老年急性肠系膜上动脉栓塞患者介入治疗的术后护理经验及并发症观察结果。术后并发症包括发生肠坏死、腹腔出血、伤口出血等。密切观察病情变化, 及时、有效地识别并发症, 采取预见性护理, 对降低病死率及促进患者康复具有重要意义。)